Ciclo Reprodutivo de Salminus hilarii VALENCIENNES, 1850 (OSTARIOPHYSI, CHARACIDAE) em um rio da região Sudeste do Brasil, SP - Aparecido Villares Junior, Gilberto (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
In this study specimens of Salminus hilarii were analyzed in the Sorocaba river basin (SP), in order to check their reproductive cycle. The samples were made every month, between September 2012 and August 2013, totaling 124 specimens collected. Females were larger and more abundant than males. Through the stages of gonadal maturation and by gonadossomatico index was determined that the reproductive period occurred during the months of November and December. This information will be important to develop management measures, awareness and preservation of an endangered species in the Upper Paraná Basin region.